Perspectives on the application of 3D motion design in marketing - Permiakova, Irina (2025)
The application of 3D motion design in marketing strategies offers a dynamic and immersive approach to engage audiences and enhance brand visibility. This abstract explores the various perspectives and benefits of integrating 3D motion design into marketing campaigns, including increased customer engagement, enhanced brand storytelling, and differentiation in a competitive landscape.